PENGARUH LATIHAN GERAK KAKI (STRETCHING) TERHADAP PENURUNAN NYERI SENDI EKSTREMITAS BAWAH PADA LANSIA DI POSYANDU LANSIA SEJAHTERA GBI SETIA BAKTI KEDIRI - Hari Poernomo, Dewi Ika Sari; Pamungkas, Yohanita (Jurnal Penelitian STIKES Kediri, 2010)
abstract backgorund : Aging is naturally experienced by human. The process includes some changes such as: biological, psychological, social, and spiritual state. Physiological alternation appears in musculoskeletal system which causes joint pain. Some treatments can be used to overcome it. One of them is stretching. Stretching increases the elasticity and strength of muscle and also reduces joint pain. The research aimed at studying the influence of stretching toward extremity of joints pain of the elderly on Posyandu Lansia Sejahtera Setia Bakti Baptist Church Kediri. Method : This research Pre Experimental Research, one group pre test – post test design. Sample was 35 respondents who met the inclusive criteria. It was taken using Purposive Sample. The variable was extremity of joints pain. The data were collected through observation and interview before and after the treatment given. Further, it was analyzed using Wilcoxon test with significant level p